Temperament and Character Differences of Patients with Polycystic Ovary Syndrome - ÖZTÜRK, AHMET; KILIÇ, ALPEREN; ÖZTÜRK, AHMET; YÜKSEL, KADRİYE BERİL; KABİL KUCUR, SUNA; DEVECİ, ERDEM; DEVECİ, ERDEM; YILMAZ, ONUR; YILMAZ, ONUR (My University, 2019)
Aim: There is an unclear relationship between Polycystic Ovary Syndrome and psychiatric disorders including anxiety and depression. We aimed to evaluate temperamental and personal characteristics of patients with PCOS.